Acute toxic effects of single dose dacarbazine: hematological and histological changes in an animal model. (November 2014) - Milijašević, B; Stefanović, D; Lalić-Popović, M; Tomić, Z; Kolarović, J; Lalošević, D; Mikov, M
Abstract Treatment of advanced soft tissue sarcoma usually includes dacarbazine (DTIC), an alkylating agent that methylates DNA and is active during all phases of the cell cycle. Common side effects of DTIC include nausea, vomiting, impaired liver and kidney function, myelosuppression, and pneumonia. There are no accounts, however, of histological and hematological changes caused by DTIC. We investigated acute hematological and morphological changes in different organs and in tumors that were caused by a single dose of DTIC. Adult Syrian golden hamsters were inoculated with a suspension of tumorigenic baby hamster kidney (BHK) cells by subcutaneous injection. On day 14 after inoculation, doses of 1.4, 1.6, 1.8 or 2.0 g/m2 DTIC were injected intraperitoneally into the hamsters. Hamsters in the control group were injected with physiological saline in the same way. Seven days after drug or saline injection the animals were sacrificed and samples of blood, heart, kidney, liver, lungs, spleen, small intestine and tumor were excised, processed and analyzed. Mitoses were counted using an ocular extension with engraved frame. Anemia, thrombocytopenia and leukocytosis were found in the control group of hamsters with fibrosarcoma, whereas animals with fibrosarcoma treated with DTIC developed anemia, thrombocytopenia and leukopenia. Severe pneumonia and moderate hepatitis were detected in all DTIC treated groups. Effects of DTIC on tumor cells included rounding and enlargement of nuclei and rarefaction of chromatin. The number of mitoses was reduced with increasing doses of DTIC. Hepatitis, myelosuppression, pneumonia, and dose-related inhibition of tumor cell proliferation were observed after a single dose of DTIC.